2009
DOI: 10.1007/s12565-009-0062-x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent hypoglossal artery with hypoplasia of the vertebral and posterior communicating arteries

Abstract: We observed a rare case of the right persistent hypoglossal artery (PHA) in the posterior cranial fossa of a deceased 74-year-old Japanese man who did not have any clinical manifestations related to this anomaly when alive. The large-sized PHA originating from the cervical internal carotid artery passed through the hypoglossal canal together with the hypoglossal nerve and reached the posterior cranial fossa to anastomose the basilar artery. In addition, the ipsilateral vertebral artery and bilateral posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“… 5 These findings have been noted by previous authors as complicating carotid endarterectomy in the context of a persistent HGA. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“… 5 These findings have been noted by previous authors as complicating carotid endarterectomy in the context of a persistent HGA. 7 , 8 …”
Section: Discussionmentioning
confidence: 99%
“… 14,15 Therefore, it is commonly associated with paroxysmal vertigo, disturbance of consciousness or cross-paralysis and other symptoms of ischaemic cerebrovascular diseases. 16 The PIA may be accompanied by other cerebrovascular abnormalities or malformations, such as hypoplasia of ICA and ECA, internal carotid-cavernous fistula, VA hypoplasia, intracranial arteriovenous malformation, intracranial aneurysm. Choudhary G analysed 21 cases of the type II PIA and found that most of them were complicated with cerebral vascular abnormalities and two cases were accompanied by aneurysms 1.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of the basilar trunk to an unusual haemodynamic stress could be the underlying mechanism that predisposes an individual to the development of aneurysms. 4 On the contrary, there is an increased risk of ischaemia caused by embolism from the internal carotid artery to the posterior circulation through the PHA. 5 Both vascular anomalies in this patient were most likely incidental findings; however, owing to the reported association of PHA with intracranial aneurysm development and ischaemic events, any new episode or the development of neurological symptoms should have triggered immediate imaging study.…”
Section: Discussionmentioning
confidence: 99%